Multiple case study on the coordination of Early Childhood Education and Primary Education teachers in the treatment of reading literary competence - Santamarina Sancho, María; Pilar; Gómez López-Quiñones, Loreto (Revista Complutense de Educación, 2024)
INTRODUCTION. Reading allows us to acquire knowledge, culture and aesthetic education; it also fosters socialisation and the development of critical thinking. However, reaching a level of competence that allows us to master it and to incorporate reading for pleasure beyond schooling requires time and effort, hence the importance of coordination between teachers at different levels to ensure that this process takes place in a methodologically consistent manner and with fluidity in relation to the evolutionary processes of the students. METHOD. This research aims at knowing the aspects in which Childhood and Primary Education teachers coordinate through the analysis of their conceptions about the concept, planning and practices of reading and literary education. For this purpose, a qualitative research has been designed, as a multiple case study, using a semi-structured clinical interview as an instrument, and content analysis and grounded theory as study methods, plus the QDA-Miner software. DISCUSSION. The conclusion is that there is need for coordination based on more up-to-date teacher training which incorporates the findings of the research available on reading and on the transition from pre-primary to primary school.